THE USE OF SIMPLE PRESENT VERB AND ADJECTIVE IN STUDENTS’ WRITING DESCRIPTIVE TEXT - Klara Ratri Bumi; Muhammad Sulhan (INFERENCE: Journal of English Language Teaching, 2020)
The Objective of this research was to analyze, know and describe the use of simple present verb on descriptive text and the use of adjective on descriptive text made by students of Public Junior High School in Bekasi. The number of population is 612. As the sample the researcher took 60 students from the population. The method used in this study was content analysis method to describe students’ errors consisting 418 erroneous sentences and analyze the data taken from written test. The finding shows that errors are 1). 56,93% or 238 errors occurred in the simple present verb and 2). 43,06% or 180 errors occurred in Adjective. It happened because the students did not really understand and they were not able to use simple present verb and adjective correctly in the sentence.